Modeling Supply Chains by Critical Paths and Leontief Input-Output Table (Global Journal of Science Frontier Research, 2022)
We formulate a supply-chain problem by:(1)casting it in the model of critical-path analysis as defined by predecessor/successor relations, and (2)allowing for mutual dependency among the activity nodes and applying Leontief's input-output structure.
Keywords: scheduling bottleneck; network disruption; pandemic disequilibria